Friction welding of small-diameter fittings and nozzles of 22K carbon steel - Yury V. Poletaev; Valery Yu. Poletaev; Victor V. Shchepkin (Advanced Engineering Research)
Introduction. The pilot study method and development of technological recommendations on friction welding (FW) of fittings and nozzles of small (up to 80 mm) diameter for welded constructions of the thermal and atomic engineering are described. The feasibility of applying the method of FW of small-diameter fittings and nozzles for the powerplant package units instead of manual arc welding (MAW) is studied. Materials and Methods. Models of fittings and nozzle units are made of low-carbon 22К steel. The selection of the angle of the conical surface preparation, the optimization of FW mode parameters, and welding of the fitting models of 40 mm in diameter are carried out on the MST-35-5 machine. Welding of nozzle models of 80 mm in diameter is implemented on the MST-41machine under the conditions of “EMK-ATOMMASH” JSC. A model structure of the nozzle unit with different angles of the conical surface is developed to select the angle of the conical surface and to optimize welding mode parameters. The dimensions of the mating interfaces angles are chosen allowing for the performance of the MST-35-5 welding machine, and for the anticipated dimensions of the fusion zone under formation which determine the weld metal quality. Research Results . The design of models and connected (conical) surfaces of fitting and nozzle units is developed. The choice of optimum angles of surfaces of preparation for welding is explained. The selection of welding parameters values is proved, and their experimental verification is carried out. Welded joints quality is tested through the nondestructive and destructive methods. The effect of the constructive and technological factors on the quality of welded joints is determined. Discussion and Conclusions . The obtained successful outcome of the pilot study has confirmed the technological capability and economic feasibility of the application of friction welding for small-diameter fittings and nozzles instead of manual arc welding with coated electrodes. Investigation of feasibility of applying FW for welding fittings and nozzles should be continued in the following directions: development of equipment; certification of the welding method; development and testing of the friction welding technology.